Analisis Perbedaan Perilaku Investasi Saham Antara Wanita dan Pria di Pasar Modal Indonesia - Feby Amalia Putri; Erly Mulyani (Jurnal Eksplorasi Akuntansi, 2023)
This study aims to analyze 1) Do women have a tendency to have low financial literacy compared to men in making stock investment decisions. 2) Do women have a tendency to be not overconfident than men in making stock investment decisions. 3) Do women have a tendency to have low risk tolerance compared to men in making stock investment decisions. 4) Do women have a tendency to herding behavior compared to men in making stock investment decisions. The novelty of this research from the previous one is that the author places more emphasis on gender differences in decision making when influenced by behavioral finance bias. This study uses quantitative methods with data collection techniques using questionnaires distributed through online media to investors with a sample of 146 investor respondents. The sample is distributed to respondents who are listed on the IDX of West Sumatra. The analytical method used in this research is descriptive analysis and Mann-Whitney test. The results of the study found 1) There is no significant difference between the financial literacy of women and men in making stock investment decisions. 2) There is a significant difference between overconfidence of women and men in making stock investment decisions, and female investors tend to be not overconfident than men in making stock investment decisions. 3) There is a significant difference between the risk tolerance of women and men in making stock investment decisions, and female investors tend to have low risk tolerance compared to men in making stock investment decisions. 4) There is a significant difference between the herding behavior of women and men in making stock investment decisions, but male investors tend to have high herding behavior compared to women in making stock investment decisions.